2002
DOI: 10.1175/1520-0485(2002)032<1914:taccbt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Antarctic Circumpolar Current between the Falkland Islands and South Georgia

Abstract: Hydrographic and lowered acoustic Doppler current profiler data along a line from the Falkland Islands to South Georgia via the Maurice Ewing Bank are used to estimate the flow of circumpolar water into the Argentine Basin, and to study the interaction of the Antarctic Circumpolar Current with the Falkland Plateau. The estimated net transport of 129 21 Sv (Sv 10 6 m 3 s 1) across the section is shared between three major current bands. One is associated with the Subantarctic Front (SAF; 52 6 Sv), and the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
84
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 26 publications
11
84
0
1
Order By: Relevance
“…The vertical structure of low temperature centred at XBT 17, with a minimum of < 1.5 °C located at about 200 m depth, suggests that this cold eddy may have been shed from the PF, as it interacts with the bottom topography. This temperature distribution is similar to that found further north along 51 o S (Arhan et al, 2002).…”
Section: Introductionsupporting
confidence: 86%
“…The vertical structure of low temperature centred at XBT 17, with a minimum of < 1.5 °C located at about 200 m depth, suggests that this cold eddy may have been shed from the PF, as it interacts with the bottom topography. This temperature distribution is similar to that found further north along 51 o S (Arhan et al, 2002).…”
Section: Introductionsupporting
confidence: 86%
“…This branch flows alongside the BC overshoot, staying in contact with NADW for an extended period and facilitating mixing between NADW and CDW. Peterson and Whitworth (1989), Arhan et al (1999), Wienders et al (2000), and Heywood and King (2002) also showed evidence of pronounced NADW influence in the CDW in the southern Argentine Basin.…”
Section: Thermohaline Structure Of the Bmcmentioning
confidence: 88%
“…4d) on the western side of the Maurice Ewing Bank (MEB), where evidence of mixing with saltier NADW is visible. At this location, Arhan et al (2002) identified an anticyclonic recirculation around the Maurice Ewing Bank that entrains NADW across the Falkland Plateau. Colder and fresher CDW that entered the Georgia Basin by circumnavigating South Georgia (SG) rather than overflowing the North Scotia Ridge ) is present at station 60 on the A23 section (Fig.…”
Section: Thermohaline Structure Of the Bmcmentioning
confidence: 99%
“…The approach stems from the momentum balance with the momentum transfer by shear from the surface to the bottom, complemented by the meridional overturning (Johnson and Bryden, 1989;Morrow et al, 1992;Gille, 1997;Tansley and Marshall, 2001, etc.). An alternative approach by Wyrtki (1960), Baker (1982), Hellerman and Rosenstein (1983) and Mestaz-Nunez et al (1992) is based on the Sverdrup balance. Both approaches are still intensively debated (Warren et al, 1996;Olbers, 1998;Gnanadesikan and Hallberg, 2000;Rintoul et al, 2001;Karsten et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is estimated from direct velocity measurements in the Drake Passage and in the southwestern Argentine Basin, above 3000 m depth, by different authors to be about 140 Sv while the geostrophic transport predicted by the geostrophic balance relative to 3000 m is only about 100 Sv. A summary of the net transport estimates based on the direct velocity measurements and on the geostrophic balance relative to 3000 m depth can be found in Whitworth et al (1982); Arhan et al (2002). The difference is commonly explained by an eastward barotropic flow velocity constituent not predicted by the geostrophic balance (Whitworth et al, 1982).…”
Section: Introductionmentioning
confidence: 99%